An electrolyte and a battery comprising the same
By using the interface protective film formed by fluorovinyl carbonate, silane borate and polycyclic esters in the lithium-ion battery electrolyte, the problem of unsatisfactory electrochemical performance of lithium-ion batteries in high and low temperature environments is solved. , achieving excellent cycle and storage performance of the battery.
Patent Information
- Application Number
- CN202411110414.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-14
AI Technical Summary
When existing lithium-ion batteries operate in high and low temperature environments, their electrochemical performance is not ideal, especially the volume expansion problem of silicon-based materials leads to instability of the interface film, which in turn affects the circulation and storage performance of the battery.
By using fluorovinyl carbonate (FEC), silane borate compounds and polycyclic esters as additives in the electrolyte, an interface protective film with excellent thermal stability, high density, flexibility and mechanical strength is formed in the electrolyte solution. , inhibit the side reaction between the negative electrode material and the electrolyte solution, and promote the free deintercalation of lithium ions.
The excellent cycle performance, high-temperature storage performance and low-temperature discharge performance of the battery at room temperature and high temperature are achieved, reducing the migration resistance of lithium ions and avoiding battery capacity attenuation and gas production.
Smart Images

Figure SMS_4 
Figure SMS_5 
Figure SMS_7
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to an electrolyte and a battery comprising the electrolyte. Background Art
[0002] With the advancement of science and technology and the diversification of energy demand, the consumption of traditional energy is accelerating. Countries are accelerating the strategic deployment of new energy technologies. Among them, power batteries are rising with the development of new energy vehicles, and energy storage batteries are also booming with the development of clean energy. Lithium-ion batteries have the advantages of being green and environmentally friendly, having good cycle performance and no memory effect. They have been widely used in the fields of electronic digital, energy storage, power vehicles, communication equipment, etc.
[0003] Carbon-based materials and silicon-based materials are the two most commonly used negative electrode materials at present, and they play a vital role in improving the application of lithium-ion batteries. However, the performance of these two materials is highly dependent on the properties of the interface film on their surface. In particular, the volume expansion problem of silicon-based materials is more prominent, and they are more dependent on the interface film.
[0004] In order to solve the above problems, researchers add new functional additives to the electrolyte to build a stable interface film on the electrode surface to protect the negative electrode material, thereby reducing the side reactions on the electrode surface. However, the existing functional additives have limited improvement on the side reactions on the electrode surface, which still makes the electrochemical performance of the battery unsatisfactory when working in high and low temperature environments. Summary of the invention
[0005] The present invention provides an electrolyte and a battery comprising the electrolyte. The electrolyte of the present invention uses fluoroethylene carbonate (FEC), a silane borate compound represented by formula I, and a polycyclic ester compound represented by formula II as additives to form an interface protection film having excellent thermal stability, high density, good flexibility, good mechanical strength, and low impedance on the surface of a negative electrode. The protection film can effectively protect the electrode from side reactions with the electrolyte and can also allow lithium ions to be freely deintercalated, thereby allowing the battery to have excellent normal temperature and high temperature cycle performance, high temperature storage performance, and low temperature discharge performance.
[0006] The first aspect of the present invention provides an electrolyte, wherein the additives include additive A, additive B and additive C; the additive A is selected from fluoroethylene carbonate, the additive B is selected from the compound shown in formula I, and the additive C is selected from the compound shown in formula II:
[0007] ;
[0008] In Formula I, R1 to R9 are each independently selected from halogen-substituted or unsubstituted C1-C8 alkyl, halogen-substituted or unsubstituted C2-C8 alkenyl, halogen-substituted or unsubstituted C2-C8 alkynyl, halogen or cyano;
[0009] In formula II, A, B, and C are each independently selected from H, a halogen-substituted or unsubstituted five-membered or six-membered cyclic carbonate, a halogen-substituted or unsubstituted five-membered or six-membered cyclic sulfate, a halogen-substituted or unsubstituted five-membered or six-membered cyclic sulfonate, or a halogen-substituted or unsubstituted five-membered or six-membered cyclic carboxylate, and at most one of A, B, and C is selected from H, and at least one of A, B, and C is selected from a halogen-substituted or unsubstituted five-membered or six-membered cyclic carbonate; L1 and L2 are each independently selected from a single bond, a halogen-substituted or unsubstituted C1-C8 alkylene, a halogen-substituted or unsubstituted C1-C8 alkenylene, or an ether bond.
[0010] In the present invention, C1~C8 alkyl refers to a saturated aliphatic hydrocarbon group with 1 to 8 carbon atoms, which can be a straight-chain alkyl or a branched-chain alkyl, including but not limited to methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, n-pentyl, n-butyl, etc.
[0011] The C2~C8 alkenyl group refers to an aliphatic hydrocarbon group with 2 to 8 carbon atoms and containing an unsaturated carbon-carbon double bond, and can be a straight-chain alkenyl group or a branched alkenyl group, including but not limited to ethenyl, propenyl, n-butenyl, isobutenyl, etc.
[0012] The C2~C8 alkynyl group refers to an aliphatic hydrocarbon group having 2 to 8 carbon atoms and containing an unsaturated carbon-carbon triple bond, and can be a straight-chain alkynyl group or a branched-chain alkynyl group, including but not limited to ethynyl, propynyl, butynyl, isobutynyl, etc.
[0013] The C1-C8 alkylene group refers to a divalent group obtained by losing two H groups in an alkane molecule having 1 to 8 carbon atoms, including but not limited to methylene, ethylene, propylene, and the like.
[0014] The C2~C8 alkenylene group refers to a divalent group obtained by losing two H atoms in an olefin molecule having 1 to 8 carbon atoms, including but not limited to vinylene, propenylene, butenylene, and the like.
[0015] Regarding the case where the above substituents are substituted by halogen, taking the halogen-substituted C1~C8 alkyl as an example, the halogen-substituted C1~C8 alkyl means that the H atom on the alkyl is further substituted by halogen, including but not limited to fluoromethyl, difluoromethyl, trifluoromethyl, chloromethyl, bromomethyl and the like.
[0016] Halogens include F, Cl, Br, and I.
[0017] The electrolyte of the present invention comprises at least three types of additives, namely, additive A, additive B and additive C. Among them, FEC as additive A can form an interface protection film including polyvinyl carbonate and LiF components on the surface of the negative electrode. Polyvinyl carbonate has good elasticity and flexibility and can inhibit the expansion of the negative electrode material during the cycle. LiF can enhance the mechanical strength of the interface protection film. However, the interface protection film is unstable under high-temperature working environment and is easy to decompose and break, resulting in oxidation-reduction side reactions between the negative electrode material and the electrolyte, serious gas generation, and thus poor battery cycle and serious capacity decay.
[0018] The Si-O covalent bond in the silane borate additive B shown in Formula I has extremely strong stability and is not easy to break and decompose at high temperatures. It is adsorbed on the surface of the interface protective film formed by FEC, improving the high-temperature stability of the interface protective film, overcoming the defect of high-temperature easy decomposition caused by FEC film formation alone, and avoiding the problem of poor cycle performance and serious capacity attenuation of the battery at high temperatures. In addition, the addition of additive B can also produce the following beneficial effects:
[0019] On the one hand, the electron-deficient B atoms in additive B can complex the transition metal ions dissolved from the positive electrode during the charge and discharge process, inhibiting the oxidative decomposition of the transition metal ions to the electrolyte;
[0020] On the other hand, the electron-deficient B atoms in the additive B can also adsorb the highly corrosive HF in the electrolyte to prevent HF from damaging the electrode material.
[0021] On the other hand, additive B decomposes itself or reacts with other additives to generate compounds with BO and BF covalent bonds embedded in the interface protective film, which is more conducive to the transmission of lithium ions, reduces the internal resistance of the battery, and thus improves the low-temperature discharge performance of the electrolyte.
[0022] However, the silane structure in the additive B will decompose the LiF in the interface protective film, resulting in a decrease in the mechanical strength of the interface protective film. The cyclic ester compound shown in Formula II includes at least two rings, and at least one ring is a cyclic carbonate. Compared with the single-ring component, the cyclic ester compound shown in Formula II has a stronger film-forming ability and can form a more dense and comprehensive interface protective film on the electrode surface, making up for the defects caused by the additive B. Since the composition of the compound shown in Formula II includes a cyclic carbonate component, the film formed by it has good compatibility with the interface protective film formed by FEC, further inhibiting the decomposition of the electrolyte on the electrode surface, so that the battery has good cycle performance.
[0023] In summary, the electrolyte of the present invention forms an interface protection film with excellent thermal stability, good mechanical strength and low impedance on the surface of the negative electrode through the synergistic effect of additives A, additive B and additive C. While the protective film effectively protects the electrode from side reactions with the electrolyte, it can also allow lithium ions to be freely deintercalated and deintercalated, thereby reducing the migration resistance of lithium ions, thereby enabling the battery to have excellent room temperature and high temperature cycle performance, high temperature storage performance and low temperature discharge performance.
[0024] In a preferred embodiment, the additive B is selected from one or more of the following compounds:
[0025] .
[0026] The silane borate compounds having the above structure can not only make the battery have good high and low temperature cycle performance, but also have the advantage of being easy to prepare. Among them, the compounds represented by Formula Ib, Formula Ic, Formula Id, Formula Ie, and Formula If also have unsaturated carbon-carbon double bonds and carbon-carbon triple bonds, which can be polymerized to form polymers to form a more comprehensive wrap on the surface of the interface protective film formed by FEC, further improving the stability of the interface protective film.
[0027] In a preferred embodiment, the additive C is selected from one or more of the following compounds:
[0028] .
[0029] When the content of additive A, additive B, and additive C in the electrolyte is too little, it is difficult to form a dense and stable interface protection film. When the content is too much, the thickness of the interface protection film will grow excessively, resulting in an increase in the internal impedance of the battery. Based on the synergistic effect of the three components and in order to make the battery have both lower impedance and form a denser and more stable interface protection film, the content of additives A, B, and C needs to be controlled within an appropriate range.
[0030] In a preferred embodiment, based on the total mass of the electrolyte, the mass content of the additive B is 0.1wt% to 1.5wt%. For example, based on the total mass of the electrolyte, the mass content of the additive B can be 0.1wt%, 0.3wt%, 0.5wt%, 0.7wt%, 0.9wt%, 1.1wt%, 1.3wt%, 1.5wt% or a range consisting of any two of these values.
[0031] In a preferred embodiment, based on the total mass of the electrolyte, the mass content of the additive C is 0.1wt% to 1.5wt%. For example, based on the total mass of the electrolyte, the mass content of the additive C can be 0.1wt%, 0.3wt%, 0.5wt%, 0.7wt%, 0.9wt%, 1.1wt%, 1.3wt%, 1.5wt% or a range consisting of any two of these values.
[0032] In a preferred embodiment, based on the total mass of the electrolyte, the mass content of the additive A is 1 wt% to 15 wt%. For example, based on the total mass of the electrolyte, the mass content of the additive A can be 1 wt%, 3 wt%, 5 wt%, 7 wt%, 9 wt%, 11 wt%, 13 wt%, 15 wt% or a range consisting of any two of these values.
[0033] Furthermore, the mass content of the additive A is not less than 20 times the mass content of the additive B.
[0034] The silane structure in additive B will decompose LiF in the interface protective film. Limiting the mass content of additive A and additive B within the above ratio range can avoid the problem of LiF component in the interface protective film formed by FEC being decomposed, resulting in a decrease in the mechanical strength of the interface protective film.
[0035] In a specific embodiment, the electrolyte of the present invention further comprises an additive D, wherein the additive D is selected from one or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), ethylene sulfate (DTD), 1,3-propane sultone (PS), 1,3-propene sultone (PST), and vinyl sulfite (ES). Additive D is a functional additive commonly used in electrolytes, and adding it to the electrolyte can further improve the cycle performance of the battery.
[0036] In a preferred embodiment, based on the total mass of the electrolyte, the mass content of additive D is 0.5wt%~5wt%. Controlling the mass content of additive D within the above range can avoid the problem of increased battery impedance caused by the transitional growth of solid electrolyte interface film (SEI) caused by excessive addition of additive D. Exemplarily, the mass content of additive D can be 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt% or a range consisting of any two of the values.
[0037] The present invention does not specifically limit the type of lithium salt in the electrolyte, and the lithium salt can be selected from the lithium salts commonly used in the electrolyte, including but not limited to lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium difluorobis(oxalatophosphate), preferably lithium hexafluorophosphate.
[0038] The present invention does not specifically limit the type of solvent in the electrolyte, and the solvent can be selected from the solvents commonly used in the electrolyte, including but not limited to propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, and butyl butyrate. One or more.
[0039] The present invention does not specifically limit the content of lithium salt in the electrolyte, as long as it is completely dissolved in the electrolyte and not easily precipitated and the electrolyte has an appropriate lithium ion concentration. For details, reference can be made to the conventional lithium salt content in the electrolyte. In a specific embodiment, based on the total mass of the electrolyte, the mass content of the lithium salt is 12wt%~15wt%. Exemplarily, the mass content of the lithium salt can be 12wt%, 13wt%, 14wt%, 15wt% or a range consisting of any two of these values.
[0040] The present invention does not specifically limit the content of the solvent in the electrolyte, as long as it can completely dissolve the lithium salt so that the electrolyte has a high ionic conductivity, and the content of the solvent in the electrolyte conventionally set in the art can be referred to. In a specific embodiment, based on the total mass of the electrolyte, the mass content of the solvent is 10wt%~80wt%. Exemplarily, the mass content of the solvent can be 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or a range consisting of any two of the above values.
[0041] A second aspect of the present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the electrolyte is the electrolyte provided by the first aspect of the present invention.
[0042] The battery of the present invention has the advantages of low internal impedance and good high and low temperature cycle performance because the electrolyte can form a dense interface protection film with excellent stability on the electrode surface and the electrolyte itself has good oxidation resistance.
[0043] In a preferred embodiment, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-based material and / or a carbon-based material.
[0044] The present invention does not specifically limit the type of silicon-based material, which may be silicon-carbon material, silicon-oxygen material, nano-silicon, silicon alloy, etc.
[0045] The present invention does not specifically limit the type of carbon-based material, which may be one or more of graphite, hard carbon, soft carbon, and mesophase carbon microbeads.
[0046] In a preferred embodiment, the negative electrode active material includes a silicon-based material, and the content of the silicon-based material in the negative electrode active material is 5 wt % to 50 wt %.
[0047] Silicon-based materials can make the negative electrode sheet have a higher gram capacity, but they are easy to expand. Controlling the content of silicon-based materials in the negative electrode active material within the above range can achieve both a smaller expansion degree and a higher gram capacity.
[0048] Furthermore, the mass content of fluoroethylene carbonate in the electrolyte is 5wt%~15wt%. FEC can effectively form a film to inhibit the expansion of silicon-based materials within the above higher content range, and after additives B and additives C are compounded with FEC within the above content range, the gas generation caused by excessive FEC content in the battery can be significantly inhibited, thereby enabling the battery to have both excellent high and low temperature cycle performance and storage performance.
[0049] The present invention does not specifically limit the type of the negative electrode current collector, which can be selected from negative electrode current collectors commonly used in the art, such as copper foil.
[0050] The negative electrode active material layer is mainly composed of negative electrode active materials and also includes conventional components such as a binder and a conductive agent.
[0051] The present invention does not particularly limit the conductive agent in the negative electrode sheet, which can be selected from conductive agents conventionally used in the art, including but not limited to one or more of acetylene black, conductive carbon black, Ketjen black, conductive graphite, carbon nanotubes, conductive carbon fibers, and graphene.
[0052] The present invention does not particularly limit the binder in the negative electrode sheet, which can be selected from binders conventionally used in the art, including but not limited to one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyethylene oxide.
[0053] The negative electrode sheet of the present invention can be prepared by conventional methods in the art, for example, dispersing the negative electrode active material, conductive agent and binder in a solvent to form a negative electrode active slurry; then coating the negative electrode active slurry on the negative electrode collector, and drying to obtain the negative electrode sheet.
[0054] In order to improve the energy density of the battery, the negative electrode sheet can be made to have a higher compaction density so that the negative electrode sheet has a higher gram capacity. In a preferred embodiment, the compaction density of the negative electrode sheet is 1g / cm 3 ~4g / cm 3 For example, the compaction density of the negative electrode sheet can be 1 g / cm 3 , 2 g / cm 3 , 3 g / cm 3 , 4 g / cm 3 Or a range consisting of any two values.
[0055] The positive electrode sheet of the present invention comprises a current collector and a positive electrode active material layer arranged on the surface of the current collector, wherein the positive electrode active material layer is mainly composed of a positive electrode active material and also comprises conventional components such as a binder and a conductive agent.
[0056] The present invention does not specifically limit the type of positive electrode active material, which can be selected from positive electrode active materials commonly used in the art, including but not limited to one or more of lithium cobalt oxide, lithium manganese oxide, nickel cobalt lithium manganese oxide ternary material, nickel manganese oxide, and lithium-rich manganese-based materials. Preferably, the nickel cobalt lithium manganese oxide ternary material.
[0057] The present invention does not particularly limit the types of the conductive agent and the binder in the positive electrode sheet. The selectable range can refer to the types of the conductive agent and the binder in the negative electrode sheet, which will not be described in detail here.
[0058] The present invention does not particularly limit the current collector in the positive electrode sheet, which can be selected from positive electrode current collectors commonly used in the art, such as aluminum foil.
[0059] The positive electrode sheet of the present invention can be prepared by conventional methods in the art, for example, dispersing the positive electrode active material, conductive agent and binder in a solvent to obtain a positive electrode active material layer slurry, and then coating the slurry on the positive electrode collector, and then drying to obtain the positive electrode sheet.
[0060] In order to improve the energy density of the battery, the positive electrode sheet can be made to have a higher compaction density so that the positive electrode sheet has a higher gram capacity. In a preferred embodiment, the compaction density of the positive electrode sheet is 2 g / cm 3 ~5 g / cm 3 For example, the compaction density of the positive electrode sheet can be 2 g / cm 3 , 2.5 g / cm 3 , 3 g / cm3 , 3.5 g / cm 3 , 4 g / cm 3 , 4.5 g / cm 3 , 5g / cm 3 Or a range consisting of any two values.
[0061] The function of the separator is to separate the positive and negative electrodes and provide a channel for the migration of lithium ions. The present invention does not specifically limit the type of separator, which can be selected from separators conventionally used in the art, such as polypropylene separators, polyethylene separators, etc.
[0062] The present invention does not specifically limit the preparation method of the lithium-ion battery, and the lithium-ion battery can be prepared by conventional preparation methods in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet, and the battery core is obtained by stacking or winding, and then the lithium-ion battery of the present invention is obtained through baking, liquid injection, formation, packaging and other processes.
[0063] The implementation of the present invention has at least the following beneficial effects:
[0064] The electrolyte provided by the present invention forms an interface protection film on the surface of the negative electrode with excellent thermal stability, high density, good flexibility, good mechanical strength and low impedance by compounding FEC, a silane borate additive shown in formula I, and a polycyclic ester additive shown in formula II. The protection film can effectively inhibit the expansion of the negative electrode material during the cycle, and can also avoid the battery capacity attenuation and gas production problems caused by the side reaction between the negative electrode material and the electrolyte. At the same time, it can also allow lithium ions to be freely deintercalated and deintercalated, reducing the migration resistance of lithium ions, thereby enabling the battery to have excellent room temperature and high temperature cycle performance, high temperature storage performance and low temperature discharge performance. DETAILED DESCRIPTION
[0065] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0066] The electrolyte and the battery provided by the present invention will be further described in detail below through specific examples.
[0067] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0068] The electrolytes and lithium ion batteries of Examples 1 to 36 and Comparative Examples 1 to 7 of the present invention were prepared according to the following method:
[0069] 1. Preparation of electrolyte
[0070] In a glove box filled with argon (water <10ppm, oxygen <1ppm), EC, DEC, and EMC were mixed in a mass ratio of 3:5:2, and then additives and LiPF6 were added. The mass content of LiPF6 was 14.5 wt% based on the total mass of the electrolyte, and the types of additives and their mass contents in the electrolyte are listed in Table 1.
[0071] 2. Preparation of positive electrode
[0072] The positive electrode active material lithium nickel cobalt manganese oxide (NCM811), the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black were mixed in a weight ratio of 96.5:2:1.5, and N-methylpyrrolidone (NMP) was added and stirred under the action of a vacuum mixer until the mixed system became a positive electrode slurry with uniform fluidity; the positive electrode slurry was evenly coated on an aluminum foil with a thickness of 7 μm; the coated aluminum foil was baked in an oven at three different temperature gradients (90°C, 100°C, and 85°C), and then dried in an oven at 120°C for 8 hours, and then roller pressed to control the compaction density of the positive electrode sheet to 3.5 g / cm 3 , cut to obtain the positive electrode sheet.
[0073] 3. Preparation of negative electrode sheet
[0074] A mixture of negative electrode active materials graphite and silicon oxide (the mass ratio of graphite to silicon oxide is 4:1), a thickener sodium carboxymethyl cellulose (CMC-Na), a binder styrene-butadiene rubber, a conductive agent acetylene black, and a conductive agent single-walled carbon nanotube (SWCNT) are mixed in a weight ratio of 95.9:1:2:1:0.1, and deionized water is added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on a copper foil with a thickness of 6 μm; after drying (temperature: 85°C, time: 5 h) and rolling, the compaction density of the negative electrode sheet is controlled to be 1.65 g / cm 3 , die-cut to obtain the negative electrode sheet.
[0075] Among them, the negative electrode active material of Examples 1 to 35 and Comparative Examples 1 to 7 is a mixture of graphite and silicon oxide (the mass ratio of graphite to silicon oxide is 4:1), and the negative electrode active material of Example 36 and Comparative Example 8 is graphite.
[0076] 4. Preparation of diaphragm
[0077] A polyethylene diaphragm with a thickness of 8 μm is used.
[0078] 5. Preparation of lithium-ion batteries
[0079] The positive electrode sheet, separator and negative electrode sheet are stacked in sequence and then wound to obtain a bare cell that has not been injected with liquid; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell. After vacuum packaging, standing, forming, shaping, sorting and other processes, a lithium-ion battery is obtained.
[0080] Table 1
[0081]
[0082]
[0083] In Table 1, the structural formula of the compound with CAS No. 1431298-10-0 is as follows:
[0084] .
[0085] Test Case
[0086] The lithium-ion battery prepared above was tested for the following properties:
[0087] 1. Capacity retention rate after 500 cycles at 25℃
[0088] Test method: At 25°C, charge the battery at 1C constant current to a cut-off voltage of 4.2V, then charge at 4.2V constant voltage to a cut-off current of 0.05C, and then discharge the battery at 1C to 2.75V, and repeat the charge and discharge for 500 cycles. Record the discharge capacity Q1 of the first week and the discharge capacity Q500 of the 500th week, and calculate the capacity retention rate of 500 cycles at 25°C by Q500 / Q1×100%.
[0089] 2. Capacity retention rate after 200 cycles at 45℃
[0090] Test method: At 45°C, charge the battery at 1C constant current to a cut-off voltage of 4.2V, then charge at 4.2V constant voltage to a cut-off current of 0.05C, and then discharge the battery at 1C to 2.75V, repeating the charge and discharge for 200 weeks. Record the discharge capacity Q1 of the first week and the discharge capacity Q200 of the 200th week, and calculate the capacity retention rate of 200 cycles at 45°C by Q200 / Q1×100%.
[0091] 3. High temperature storage performance
[0092] Test method: At 25°C, charge the battery at a constant current of 1C to a cut-off voltage of 4.2V, then charge at a constant voltage of 4.2V to a cut-off voltage of 0.05C, and then discharge the battery at a constant current of 0.5C to 2.75V, and the discharge capacity is recorded as C2. Then charge at a constant current of 1C to 4.2V, and charge at a constant voltage of 4.2V to a cut-off current of 0.05C. Then transfer the battery to a high temperature of 60°C and place it for 7 days, and then discharge it at a constant current of 0.5C, and the discharge capacity is recorded as C3. The capacity retention rate of the battery stored at 60°C for 7 days is calculated by C3 / C2×100%.
[0093] The initial thickness of the battery after capacity division is recorded as h1, and the thickness after being stored at a high temperature of 60°C for 7 days is h2. The thickness expansion rate of the battery stored at 60°C for 7 days is calculated by (h2-h1) / h1×100%.
[0094] 4. DC internal resistance (DCIR) growth rate
[0095] Test method: At 25°C, charge the battery to 4.2V at 1C constant current, leave it for 5 minutes, then discharge it at 1C for 30 minutes, leave it for 1 hour, and then discharge it at 2C (I 2C ) discharge for 10s, record the voltage values V1 and V2 before and after 2C discharge, and calculate the DCIR1 of the battery at 50% SOC (the calculation formula of DCIR1 is: DCIR1=(V1-V2) / I 2C After the battery was stored at 60°C for 7 days and charged and discharged at 1C constant current for 3 weeks, it was charged to 4.2V at 1C constant current, left for 5 minutes, then discharged at 1C for 30 minutes, left for 1 hour, and then discharged at 2C (I 2C ) discharge for 10s, record the voltage values V3 and V4 before and after 2C discharge, and calculate the DCIR2 of the battery at 50% SOC (the calculation formula of DCIR2 is: DCIR1=(V3-V4) / I 2C ). DC internal resistance (DCIR) growth rate = (DCIR2- DCIR1) / DCIR1*100%.
[0096] 5. Low temperature discharge performance test
[0097] Test method: At 25°C, charge the battery to 4.2V at 1C constant current and constant voltage, until the cut-off current is 0.05C, discharge at 1C constant current to 2.75V, and record the discharge capacity as Q1. At 25°C, charge the battery to 4.2V at 1C constant current and constant voltage, until the cut-off current is 0.05C, and then discharge the battery to 2.75V at 1C at -20°C, and record the discharge capacity of the battery as Q2. -20°C discharge capacity retention rate = Q2 / Q1*100%.
[0098] The test results of the above performance are shown in Table 2.
[0099] Table 2
[0100]
[0101] The following conclusions can be drawn from the data in Table 2:
[0102] 1) According to the comparison of Examples 1 to 5 and Comparative Example 4, it can be seen that when FEC is not added, the cycle performance of the battery at 25°C and 45°C and the discharge capacity retention rate at -20°C are significantly poor. After adding FEC, a SEI film can be formed on the surface of the negative electrode, which helps to improve the cycle performance of the battery at high and low temperatures. However, when the FEC content is too little, the film formation quality is poor, and its room temperature and high temperature cycle performance are relatively poor. When the FEC content is too high, it is difficult to effectively suppress the gas production of the battery, resulting in a significant increase in the thickness expansion rate and DCIR stored at 60°C, and a significant deterioration in the cycle performance of the battery at 45°C.
[0103] 2) From the comparison between Examples 3, 6 to 10 and Comparative Examples 1 and 3, it can be seen that the silane borate additives B with different substituents can make the battery have excellent 25°C and 45°C cycle performance, low-temperature discharge performance, and overall have a lower 60°C storage thickness expansion rate, DCIR growth rate and low-temperature discharge capacity retention rate. When tri-tert-butyl borate is used as additive B without a silane structure, the stability of the SEI film at high temperature cannot be improved, resulting in the battery decomposing and producing gas at high temperature, severe growth of DCIR, and significantly poor cycle performance at 45°C and storage performance at 60°C. When additive B is not contained, the battery not only produces severe gas, resulting in significant deterioration of high temperature performance and storage performance, but also its low-temperature discharge performance is significantly reduced.
[0104] 3) From the comparison of Examples 3 and 11 to 14, it can be seen that when the amount of silane borate additive B added is too small, it is difficult to effectively inhibit the expansion of the negative electrode material, and the battery impedance is large, resulting in poor high temperature performance and low temperature discharge performance of the battery. When the amount of silane borate additive B added is too large, the battery impedance increases significantly, and the battery's 25°C and 45°C cycle performance decreases significantly. In addition, during high-temperature storage, the interface film constructed with the participation of additive B can effectively inhibit side reactions, and thus still has good storage capacity retention, lower gas production and lower DCIR growth rate.
[0105] 4) From the comparison of Examples 3, 15 to 22 and Comparative Examples 2, 5, and 6, it can be seen that when additive C is not added, the cycle performance of the battery at 25°C and 45°C is relatively poor, while the use of additive C with different substituent types can make the battery have excellent high and low temperature cycle performance, high temperature storage performance and low temperature discharge performance. However, when monocyclic vinyl sulfate or bicyclic vinyl sulfate is used, it is difficult to effectively inhibit the expansion of the negative electrode material, and the battery's 25°C and 45°C cycle performance is relatively poor.
[0106] 5) From the comparison of Examples 3 and 23 to 26, it can be seen that the content of additive C should not be too high. When the content of additive C increases, the battery impedance increases significantly, resulting in a certain deterioration in room temperature and high temperature cycle and low temperature discharge performance.
[0107] 6) From the comparison of Examples 3 and 27 to 35, it can be seen that when an appropriate amount of additive D with film-forming function such as VC, VEC, DTD, PS, PST, ES, etc. is further added on the basis of additives A, B, and C, the cycle performance of the battery at 25°C and 45°C, the storage performance at 60°C and the low-temperature discharge performance are improved. From the comparison of Example 27 and Examples 33 to 35, it can be seen that when the content of additive D is too high, the internal resistance of the battery increases significantly, resulting in poor cycle performance at room temperature and high temperature. The reason may be that when the content of additive D increases, it will lead to excessive growth of the SEI film, thereby increasing the impedance.
[0108] 7) From the comparison between Example 3 and Comparative Example 7, it can be seen that when the electrolyte includes only 10% FEC as an additive, the gas production phenomenon of the battery is serious, the thickness expansion rate and DCIR at 60°C are significantly increased, and the cycle performance of the battery at 25°C and 45°C and the low-temperature discharge performance at -20°C are significantly deteriorated.
[0109] 8) By comparing Example 36 and Comparative Example 8, it can be seen that when the negative electrode active material is graphite, the use of FEC in combination with Additive B and Additive C (Example 36) can enable the battery to obtain excellent cycle performance at 25°C and 45°C, storage performance at 60°C, and low-temperature discharge performance at -20°C.
[0110] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An electrolyte comprising a solvent, a lithium salt and an additive, characterized in that: The additives include additive A, additive B and additive C; the additive A is selected from fluoroethylene carbonate, the additive B is selected from one or more of the compounds shown in formula Ib, the compounds shown in formula Ic, the compounds shown in formula Id, and the compounds shown in formula If, and the additive C is selected from the compounds shown in formula II: ; ; In formula II, A, B, and C are each independently selected from H, halogen-substituted or unsubstituted five-membered or six-membered cyclic carbonates, halogen-substituted or unsubstituted five-membered or six-membered cyclic sulfates, halogen-substituted or unsubstituted five-membered or six-membered cyclic sulfonates, and halogen-substituted or unsubstituted five-membered or six-membered cyclic carboxylates, and at most one of A, B, and C is selected from H, and at least one of A, B, and C is selected from halogen-substituted or unsubstituted five-membered or six-membered cyclic carbonates; L1 and L2 are each independently selected from a single bond, a halogen-substituted or unsubstituted C1-C8 alkylene, a halogen-substituted or unsubstituted C2-C8 alkenylene, or an ether bond; The additive C is selected from one or more of the following compounds: ; Based on the total mass of the electrolyte, the mass content of the additive B is 0.1wt%~1.5wt%; Based on the total mass of the electrolyte, the mass content of the additive C is 0.1wt%~1.5wt%; Based on the total mass of the electrolyte, the mass content of the additive A is 1wt%~15wt%.
2. The electrolyte according to claim 1, characterized in that The mass content of the additive A is not less than 20 times the mass content of the additive B.
3. The electrolyte according to claim 1, characterized in that The electrolyte further includes an additive D, and the additive D is selected from one or more of vinylene carbonate, vinyl ethylene carbonate, ethylene sulfate, 1,3-propane sultone, 1,3-propylene sultone, vinyl sulfite, and tris(trimethylsilyl)phosphate.
4. The electrolyte according to claim 3, characterized in that Based on the total mass of the electrolyte, the mass content of the additive D is 0.5wt%~5wt%.
5. The electrolyte according to claim 1, characterized in that The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium difluorobis(oxalatophosphate); And / or, the solvent is selected from one or more of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate and butyl butyrate.
6. The electrolyte according to claim 5, characterized in that Based on the total mass of the electrolyte, the mass content of the lithium salt is 12wt%~15wt%; And / or, based on the total mass of the electrolyte, the mass content of the solvent is 10wt%~80wt%.
7. A battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The electrolyte is the electrolyte according to any one of claims 1 to 6.
8. The battery according to claim 7, characterized in that The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material. The negative electrode active material includes a silicon-based material and / or a carbon-based material.
9. The battery according to claim 8, characterized in that The negative electrode active material includes a silicon-based material, and the content of the silicon-based material is 5wt% to 50wt%.
10. The battery according to claim 8 or 9, characterized in that: The mass content of fluoroethylene carbonate in the electrolyte is 5wt%-15wt%.
